Research on Training Path of Taiji Health Professionals Under the Concept of Big Health - Bo, Song; Ding, Guanrong (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Purpose: Great health, as an important health concept, has gradually attracted wide attention around the world. It extends the concept of health from the absence of disease to the balance of body and mind, and the harmony of social relationships. The concept of Big Health goes beyond the traditional medical model and emphasizes the importance of comprehensive health, overall happiness and quality of life. The focus is not only on the treatment of disease, but also on prevention, health maintenance and lifestyle improvement, including physical, mental and social health. As an effective health practice method, Taiji health is being integrated with the concept of big health, which provides a beneficial path for modern society. However, the training path of Taiji health professionals is still facing a series of challenges, which need to be further studied and improved. On the one hand, this study is helpful to understand the application and promotion of the concept of big health in the field of Tai chi health, and provide people with more choices of health maintenance and promotion. On the other hand, it is helpful to improve the quality and standard of Tai chi health care practice and provide the society with more professionally trained Tai chi health care practitioners. In addition, this study also helps to deepen the understanding of the concept of big health and provide new ideas for the realization of comprehensive health. Methods: Using logical analysis, literature and other research methods, the training path of Taiji health professionals under the concept of big health was studied. Results: At present, the difficulties in the training of Taiji health professionals are as follows: First, the education system is not perfect. Tai Chi health care is a diverse field, covering sports science, psychology, traditional Chinese health and other aspects of knowledge and skills. However, at present, there is a lack of unified educational standards and curriculum systems, and different educational institutions and training programs can not unify the teaching content and methods. This has led to differences in the education received by students in different schools or training institutions, making it difficult to form uniform standards and recognition within the industry. Second, curriculum standards are not uniform. The inconsistency of curriculum standards in the field of Tai chi health care is an important problem that affects the quality of professional personnel training and industry standardization. The existence of this problem is closely related to many factors. Tai Chi health care covers many sub-fields such as Tai Chi and traditional Chinese medicine, and each sub-field has a rich theory and practice system. Due to the diversity and complexity of Taiji health disciplines, different courses may focus on different aspects, which leads to the diversity of curriculum standards, and it is difficult to achieve unity. Third, clinical practice is lacking. The clinical practice of Tai Chi wellness requires suitable venues and facilities so that students can apply the knowledge and skills they have learned in a practical setting. However, many educational institutions and training programs lack appropriate clinical practice sites, which makes it difficult for students to obtain adequate practice opportunities. Some schools may not be equipped with tai chi health laboratories or professional practice sites, which limits the practical experience of students. Fourth, interdisciplinary training is insufficient. Tai Chi health care covers many disciplines, including sports science, traditional Chinese medicine, psychology and so on. However, in the education system, these subject areas are usually segregated and develop independently. This leads to the lack of interdisciplinary training, and students often can only acquire knowledge in specific subject areas, but it is difficult to obtain interdisciplinary comprehensive education. Interdisciplinary training requires cooperation and exchange in different subject areas. However, the current lack of opportunities and platforms for interdisciplinary collaboration makes it difficult for students to interact and collaborate with faculty and students in other subject areas. Conclusion: The training path for Taiji health professionals is to improve the training and education system. A unified educational standard and curriculum system should be formulated, including requirements for the transfer of interdisciplinary knowledge and the mastery of skills, to ensure that students receive a comprehensive education in the field of Tai chi health. Combine with national health education standards to provide guidance and supervision. Strengthen the construction of teaching staff. Improving the quality of teaching staff is the key to training Taiji health professionals. Teachers with interdisciplinary knowledge background should be recruited, and interdisciplinary training opportunities should be provided for teachers. Unify the curriculum standards for personnel training, comprehensively consider the setting of core courses and elective courses, and gradually build a comprehensive Tai chi health education system. The core courses ensure that students have acquired the basic knowledge and skills in the field of Tai Chi health care, while the elective courses allow students to further their learning according to their needs and interests. Enhancing students' practical clinical experience and enhancing the ways and paths of students' practical clinical experience play a key role in the training of Taiji health professionals. In order to better meet the requirements of the Big health concept, a variety of measures can be taken. First of all, provide students with sufficient clinical practice opportunities. Achieved through partnerships with hospitals, rehabilitation centers, community health programs, etc., such internship experiences enable students to have hands-on contact with different types of patients, learn how various health problems are handled, and improve clinical operational skills. Secondly, strengthen the implementation of clinical case analysis course. By analyzing real clinical cases, students can gain a deeper understanding of the process of disease diagnosis and treatment. By participating in discussions, making treatment suggestions, and thinking about the patient's recovery plan with teachers and classmates. Promoting interdisciplinary personnel training. First of all, interdisciplinary curriculum design is the key to cultivate interdisciplinary talents. Schools can offer interdisciplinary courses that combine knowledge in the field of Tai chi health with related disciplines such as sports science, traditional Chinese medicine, and psychology. Teachers in different subject areas are encouraged to collaborate on teaching and research projects to develop students' ability to think and collaborate across disciplines. Establish an interdisciplinary tutor system, assign interdisciplinary tutors to students, provide one-on-one guidance and support, help students plan their learning paths, recommend interdisciplinary courses and research projects, and guide students to conduct interdisciplinary research.